The Impact of Learning Dacilities and Learning Discipline for the Result Grade VII SMP Negeri 7 Pematang Siantar - Ivan Rivaldo Purba; Anton Luvi Siahaan; Sotarduga Sihombing (MultiTech Publisher, 2023)
This research aims to find out how learning facilities and discipline influence the learning outcomes of class VII students at SMP Negeri 7 Pematang Siantar. The variables in this research are learning facilities and discipline as independent variables and learning outcomes as dependent variables. This type of research is quantitative descriptive research, with a population of all class VII students at SMP Negeri 7 Pematang Siantar totaling 222 . students and the research sample was 145 students selected using random sampling techniques . Data collection techniques use observation and questionnaires, while data analysis techniques use validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity, multiple linear regression, t tests, f tests, and coefficient of determination tests (R2). ​The results of this research indicate that there is no positive and significant influence between learning facilities on the learning outcomes of class VII students at SMP Negeri 7 Pematang Siantar as seen from the tcountl<ttable or 1.032<1.6556. There is a positive and significant influence between learning discipline on the learning outcomes of class VII students at SMP Negeri 7 Pematang Siantar as seen from the value of tcount>ttable or 3.338> 1.6556 . There is a positive and significant influence between learning facilities and discipline on the learning outcomes of class VII students at SMP Negeri 7 Pematang Siantar as seen from the fcount>ftable value or 6.416>3.06 and the significant value is 0.001<0.05.